Fertility Preservation: Current and Future Perspectives for Oncologic Patients at Risk for Iatrogenic Premature Ovarian Insufficiency. (11th July 2018) - Pinelli, Sara; Basile, Stefano
Abstract : Progress in recent years in the efficacy of oncologic treatment and early diagnosis of cancer has determined an increase in life expectance in cancer patients. About 10% of all cancer cases affect women younger than 45 years; therefore nowadays approximately 5-6% of the population in childbearing age consists in cancer survivors. A crucial issue is the high risk of premature ovarian insufficiency due to possible gonadotoxic effects of oncologic treatments. Considering combined chemotherapy, radiation therapy, and bone marrow transplantation, this risk can reach 92-100%, depending on the age and ovarian reserve of the patient, as well as the schedule and type of therapy. International guidelines recommend addressing all the patients diagnosed with a neoplasia treatable with potentially gonadotoxic therapies to fertility preservation. Moreover, fertility preservation also seems to reserve fascinating implications for women who want to delay childbearing for social reasons or women affected with endometriosis, who could receive unexpected opportunities. At present, the most widespread techniques to preserve fertility in adult women are embryo or oocyte cryopreservation, depending on the presence of a partner or according to legislative issues, but these procedures require time for ovarian stimulation. In prepubertal patients or when there is no possibility of delaying chemotherapy, ovarian tissue cryopreservation and subsequent transplantation represent the main strategy.